Risk Factors for Childhood Leukemia: a Comprehensive Literature Review - Vasileiou, Panagiota; Charalambous, Andreas (My University, 2012)
Background: Although overall incidence is rare, leukemia is the most common type of childhood cancer. It accounts for 30% of all cancers diagnosed in children younger than 15 years. Child leukaemia has been related to external factors to which children are exposed during their lives as well as internal factors. Aim: The aim of the present study was to explore the risk factors for childhood leukemia. Method and Material: An electronic search of CINAHL and PubMed was undertaken, along with citation searches. Studies were selected if risk factors for childhood leukaemia were described in the title or abstract and original data were included. Study quality was taken into consideration. Results: The search produced 1726 articles from which 26 articles met the inclusion criteria. Several internal and external risk factors for childhood leukaemia were identified in this review. These factors included the magnetic fields and high voltage transmission lines, parental occupational exposure (to chemicals), nuclear power plants and ionising radiation, intramuscular vitamin K, population mixing and endogenous factors including baby weight. Conclusions: Most risk factors have been found to be weakly and inconsistently associated with either form of acute childhood leukemia. Only one environmental risk factor (ionizing radiation) has been significantly linked to acute lymphocytic leukaemia or acute myelogenous leukaemia. Knowledge of these particular risk factors can be used to support measures to reduce potentially harmful exposures and decrease the risk of disease.
Keywords: Children; Leukemia; Risk Factors; Children and the environment; Childhood